Science, society, and policy in the face of uncertainty: reflections on the debate around face coverings for the public during COVID-19. Issue 5 (19th October 2020) - Martin, Graham P.; Hanna, Esmée; McCartney, Margaret; Dingwall, Robert
ABSTRACT: The COVID-19 pandemic has had enormous effects on health, wellbeing, and economies worldwide. Governments have responded with rapid and sometimes radical public health interventions. As nations grapple with the question of how to regain normality without unnecessarily endangering lives or healthcare systems, some scientists have argued for policies to encourage or compel the use of face coverings in community (non-clinical) settings, despite acknowledged gaps in the evidence base for the effectiveness of such a measure. This commentary has two objectives. First, in the face of strong arguments that face coverings are a commonsense intervention, with negligible downsides, that can only do good, we make the case for caution in changing policy. Many seemingly benign public health interventions have the potential to cause harm, and that harm is often socially differentiated. We present five arguments for caution in policy change. Second, we reflect on the wider implications of the increasingly overt approaches to policy advocacy taken by some scientists. Drawing from the theory of post-normal science, we argue that the science–policy interface in the case of face coverings has taken a surprisingly traditional form, falling short of interdisciplinary integration and failing to incorporate insights of the full range of relevant experts and affected stakeholders. We sketch a vision for an alternative, more mature, relationship between science and society that accepts uncertainty, embraces deliberation, and rises to the challenge of developing knowledge to improve public health.